Metabolic, Molecular, and Behavioral Effects of Western Diet in Serotonin Transporter-Deficient Mice: Rescue by Heterozygosity? - Veniaminova, Ekaterina; Cespuglio, Raymond; Chernukha, Irina; Schmitt-Boehrer, Angelika G.; Morozov, Sergey; Kalueff, Allan V.; Kuznetsova, Oxana; Anthony, Daniel C.; Lesch, Klaus-Peter; Strekalova, Tatyana (Frontiers in Neuroscience, 2020)
Reduced function of serotonin transporter (SERT) is associated with an increased susceptibility to anxiety and depression, and in aged females, with type-2 diabetes. Preference for “Western diet” (WD), enriched with saturated fat, cholesterol and sugars may aggravate these conditions. We investigated metabolic, molecular and behavioural changes in 12 months-old female mice, with a heterozygous (Sert+/-: HET) and complete inactivation (Sert-/-: KO) of the Sert (Slc6a4) gene in comparison with wild-type mice (Sert+/+: WT), after a 3-week housing on WD or control diet. Earlier, decreased glucose tolerance, central and peripheral inflammation, dyslipidaemia, emotional, cognitive and social abnormalities were reported in WD-fed young female mice. Here, most of these hallmarks of a WD-induced syndrome, including brain overexpression of inflammatory marker toll-like receptor 4 (Tlr4), impaired hippocampus-dependent performance in the marble test, were found in the WT-WD and KO-WD groups, but not in HET-WD mice. However, all WD-groups displayed obesity, increased scores of depressive-like behaviour in the swim test and other changes associated with metabolic syndrome in employed mouse model. Naïve KO mice demonstrated impaired hippocampus-dependent performance, increased brain expression of serotonin receptor Htr2c and Htr1b, as well as Tlr4 and mitochondrial regulator, peroxisome proliferator-activated receptor gamma-coactivator-1a (Ppargc1a). Paradoxically, these and other changes were reversed in KO-WD mutants, suggesting a complex interplay between Sert deficiency and metabolic factors as well as potential compensatory molecular mechanisms that might be disrupted by the WD exposure. Most, but not all of the changes in gene expression in the brain and liver of KO mice were not found in HET mice, under normal conditions or after WD-exposure. Thus, complete versus partial Sert inactivation in aged mice results in different metabolic, molecular and behavioural consequences following WD challenge. While some dietary-induced changes were similar in KO-WD and HET-WD mice, the latter displayed a “rescued” phenotype in terms of dietary-induced abnormalities in glucose tolerance, neuroinflammation and hippocampus-dependent behaviour. Our findings support the view of increased resilience of Sert+/- mice to various adversities reflecting the concept of heterosis as evolutionary adaptive mechanism.